Unresolvable Disagreements in Carnap's Metametaphysics. (22nd April 2021) - Vrahimis, Andreas
Abstract: Carnap's 1931 attack against metaphysics notoriously utilises Heidegger's work to exemplify the meaninglessness of metaphysical pseudo‐statements. This paper interprets Carnap's metametaphysics as concerned with delimiting theoretical dialogue in such a manner as to exclude unresolvable disagreements. It puts forth a revised version of Carnap's argument against the viability of metaphysics, by setting aside his stronger claims that rely on verificationism and focusing instead on his account of metaphysical claims as mere expressions of what he calls "Lebensgefühl, " or a general attitude towards life. Such attitudes, Carnap argues, are unsuitable objects of theoretical dialogue, insofar as disagreements that concern them are unresolvable. Carnap thus recommends abandoning the attempt to resolve metaphysical disagreements as if they were theoretical. As long as it does not enter into unresolvable disagreements, art, rather than theory, is the appropriate medium for expressing Lebensgefühl .